2015
DOI: 10.1073/pnas.1424279112
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven synchrony of Prochlorococcus growth and mortality in the subtropical Pacific gyre

Abstract: Theoretical studies predict that competition for limited resources reduces biodiversity to the point of ecological instability, whereas strong predator/prey interactions enhance the number of coexisting species and limit fluctuations in abundances. In open ocean ecosystems, competition for low availability of essential nutrients results in relatively few abundant microbial species. The remarkable stability in overall cell abundance of the dominant photosynthetic cyanobacterium Prochlorococcus is assumed to ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
156
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(190 citation statements)
references
References 37 publications
28
156
3
1
Order By: Relevance
“…Several recent studies suggest a previously underappreciated importance of closely coupled diurnal oscillations as the underlying mechanisms of ecosystem stability in open ocean food webs (Ottesen et al, 2014;Ribalet et al, 2015). Our results show strong diurnal variability in photophysiology and cell metabolism of mixed phytoplankton assemblages.…”
Section: Discussionsupporting
confidence: 61%
“…Several recent studies suggest a previously underappreciated importance of closely coupled diurnal oscillations as the underlying mechanisms of ecosystem stability in open ocean food webs (Ottesen et al, 2014;Ribalet et al, 2015). Our results show strong diurnal variability in photophysiology and cell metabolism of mixed phytoplankton assemblages.…”
Section: Discussionsupporting
confidence: 61%
“…For example, laboratory studies with Prochlorococcus isolates indicated maximal growth rates of ~0.6 d −1 (Liu et al 1995, Moore et al 1995, Claustre et al 2002. In a study in the subtropical North Pacific, Ribalet et al (2015) estimated Prochlorococcus growth rates ranging from 0.2 to 0.9 d −1 based on diel changes in cell size and abundances. Measurements from the California coast reported growth rates estimated from dilution experiments to be ~0.7 d −1 for Synechococcus and ~1 d −1 for PPE (Worden et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the growth and mortality of Prochlorococcus in the subtropical Pacific gyre was found to be synchronized to the light-dark cycle, with the highest mortality rate at night (Ribalet et al, 2015). This could be explained by light-dark synchronized infection of Prochlorococcus by cyanophages, although synchronized grazing by protists is also possible (Ribalet et al, 2015).…”
Section: Diel Oscillations In Cyanophage Abundance In Aquatic Environmentioning
confidence: 99%